Focus on Antibiotics – New Challenges and Steps Forward in Discovery and Development - Rusu, Aura; Uivarosi, Valentina; Tanase, Corneliu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Focus on Antibiotics - New Challenges and Steps Forward in Discovery and Development" addresses the latest efforts towards discovering new antibiotics. The articles in this Special Issue cover various topics concerning antibacterial drugs. They provide valuable insights into the challenges and opportunities facing the field of antibiotic research and offer innovative solutions to tackle the growing problem of antibiotic resistance. The content of this Special Issue addresses antibacterial quinolones of the latest generation, new tetracyclines (such as glycylcyclines, aminomethylcyclines, and fluorocyclines), metal complexes (Ru (II/III) frameworks and Co(III) complexes with diamine chelate ligands), various nanoparticles (gold, silver and titanium dioxide nanoparticles), bioactive compounds produced by Mixobacterials species, anti-mycobacterial compounds acting as phosphopantetheinyl transferase inhibitors. The research in this Special Issue will contribute to pharmaceutics and ultimately contribute to developing new and effective antibiotics. We are grateful to the authors for their contributions and hope this Special Issue will stimulate further research and discussion on antibiotics. We also thank the reviewers for their time and expertise, and the editorial team for supporting this Special Issue. Finally, we hope this Special Issue will serve as a valuable resource for researchers, clinicians, and policymakers working towards a future where antibiotics remain vital in our fight against infectious diseases.